2021
DOI: 10.3389/fendo.2021.755231
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Indicators of Non-Transection Nerve Injury and Vocal Fold Motion Impairment After Thyroid Surgery – Correlation Between Intraoperative Neuromonitoring Findings and Perioperative Voice Parameters

Abstract: ObjectivesIn patients with recurrent laryngeal nerve (RLN) injury after thyroid surgery, unrecovered vocal fold motion (VFM) and subjective voice impairment cause extreme distress. For surgeons, treating these poor outcomes is extremely challenging. To enable early treatment of VFM impairment, this study evaluated prognostic indicators of non-transection RLN injury and VFM impairment after thyroid surgery and evaluated correlations between intraoperative neuromonitoring (IONM) findings and perioperative voice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…From the results of this study, it can be found that permanent VC palsy rarely occurred in nerve injuries caused by traction or dissecting trauma, but there was a high rate of permanent VC palsy (40%, 2/5) in thermal injuries. The voice outcome and VC mobility prognosis are worse in patients with thermal RLN injuries than in those with mechanical RLN injuries ( 30 , 31 ). Therefore, the use of EBDs or electrocauterization near the RLN should pay special attention to the safety distance.…”
Section: Discussionmentioning
confidence: 99%
“…From the results of this study, it can be found that permanent VC palsy rarely occurred in nerve injuries caused by traction or dissecting trauma, but there was a high rate of permanent VC palsy (40%, 2/5) in thermal injuries. The voice outcome and VC mobility prognosis are worse in patients with thermal RLN injuries than in those with mechanical RLN injuries ( 30 , 31 ). Therefore, the use of EBDs or electrocauterization near the RLN should pay special attention to the safety distance.…”
Section: Discussionmentioning
confidence: 99%
“…None of the above studies included [32] or managed to correlate [21] IONM results and FFL findings to predict progression of transient VFP to permanent. While, in an intriguing study by Huang et al [22], IONM findings and perioperative voice parameters were examined to predict voice outcomes and can perhaps be applied on future ENT protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Predictive factors for permanent VFP differ among studies depending on instruments, such as laryngeal electromyography [19, 20] or laryngostroboscopy [21], and protocols, such as voice indexes [22], implemented. Although the results of such studies have individually identified possible predictive factors, due to the variability of methods applied or their complexity, none has gained general consensus or has been widely applied.…”
Section: Introductionmentioning
confidence: 99%
“…High temperatures are unavoidable when using EBDs, and direct or indirect thermal energy can transfer to the recurrent laryngeal nerve (RLN) and result in thermal injury (3)(4)(5). RLN thermal injury causes more irreversible impairment of vocal cord movement than RLN mechanical injury, resulting in more voice disturbance (6,7).…”
Section: Introductionmentioning
confidence: 99%